Academic achievement and self-perception, motivation, goal valuation, and school attitude among students in high and low SES - Quinto, Miguel P. (College of Education, University of the Philippines Diliman, 2021)
This study investigates the relationship between school attitudes and academic achievement with reference to students' SES. The research also looks into the interrelations among the school attitudes, how their interactions affect academic achievement, and the factors that shape them. The study utilizes a mixed methods research design and uses data from Grades 11 and 12 male students with high and low SES from a Philippines private school. Results show that students with low SES had significantly higher general weighted averages compared to those with high SES. As explanation for their higher grades, data points to the significantly better school attitudes among the former set of students. They have higher academic self-perceptions, which was found to have a significant direct effect on academic achievement. They also have better motivation/self-regulation, attitude towards school, and attitude toward teachers/classes, the interaction among which was also found to have a significant effect on achievement. In addition, the students in the low SES group have higher ratings on goal valuation. Although findings suggest that it has no direct effect on achievement, goal valuation may have an indirect influence through its positive effects on student motivation and self-regulation. Various factors that shape the five school attitudes are also discussed. A crucial observation is that social support from teachers and parents is important for students' motivation and attitudes toward school and teachers. This findings is significant for students in low SES groups. The impact of the support they received from teachers and especially parents on their attitudes and academic achievement are highlighted.